AKTIVITAS WHALING OLEH JEPANG DI KAWASANANTARTIKA BERDASARKAN INTERNATIONAL CONVENTION FOR THE REGULATION OF WHALING (ICRW) 1946: Whaling Activities by Japan in the Antartic Region based on theInternational Convention for the Regulation of Whaling (ICRW) 1946 - Dwinanda Audrey; Amalia Zuhra (Faculty of Law, Universitas Trisakti, 2025)
The International Convention for the Regulation of Whaling (ICRW) 1946 was established to protect whale populations. Although Japan is a party to the convention, its whaling—originally a cultural practice—has developed into a commercial activity supported by modern technology, with operations expanding into the Antarctic region. This study examines whether Japan’s activities in the Antarctic comply with the ICRW 1946 and how state responsibility should be applied. Using normative legal research with a descriptive-analytical approach and deductive reasoning, the study finds that Japan’s whaling programs, particularly JARPA and JARPA II, violate the provisions of the ICRW because they do not meet the criteria for legitimate scientific research. Consequently, Japan bears responsibility in the form of strict liability, requiring proof of negligence in natural resource management and compensation through restitution.